Alterações na Articulação Temporomandibular após cirurgia ortognática diagnosticada com uso de Ressonância Magnética - Oliveira, Mirlany Mendes Maciel (2024)
The temporomandibular joint is considered one of the most complex joints in the human body and can be affected by the same diseases and disorders that affect other joints of the musculoskeletal system, such as disc displacements, degenerative joint diseases, inflammatory arthritis and synovitis. The effects of orthognathic surgery on the temporomandibular joint, especially the changes that occur postoperatively, remain incompletely understood. Orthognathic surgery in patients with temporomandibular disorders can be challenging, as it is important to correct skeletal malformations, but also to reduce arthralgia, muscle pain and temporomandibular disorders. The present study seeks to carry out, through a systematic review, summarize the available evidence and answer the following question “What is the effect of Orthognathic Surgery on the position of the Joint Disc of the Temporomandibular Joint in patients with dentofacial deformity?”. An electronic search in seven databases primary(Embase, Cochrane Library, MedLine via PubMed, SciELO, Scopus, LILACS and Web of Science) and two additional (EASY and MedRxiv) to partially capture "gray literature". The PICO strategy identified articles without restrictions on language or year of publication. Two reviewers extracted the data, assessed the risk of bias of the individual study using the JBI Manual. 4,024 records were found, seven met the eligibility criteria and the bibliographic references of eligible articles were evaluated, two eligible articles were found and added to this systematic review, totaling nine articles included, published between 1997 and 2020. Although the majority of articles included in this systematic review did not notice significant changes in the position of the articular disc after orthognathic surgery, there are articles that observed changes in the position of the articular disc, especially in cases of articular disc displacement with reduction.